Analyzing User Satisfaction of a Study Abroad Guidance Company Website Using the Customer Satisfaction Index (CSI) Method - Nispi, Fajrian; Kurniawati, Ana; Wulandari, Lily (JURNAL TEKNIK INFORMATIKA, 2024)
XYZ is an education technology company dedicated to assisting Indonesian students in gaining acceptance to universities worldwide through full scholarship, partial, or self-funding. Until 2024, XYZ has a thousand alumni accepted in 46 countries and many universities worldwide. One of the marketing trackers that XYZ has is the website. With this website, the company will deliver the service to customers and receive user feedback to run and improve their services. The measurement of user satisfaction level can be used to improve the quality of service in digital media. The method used in this study to measure user satisfaction level is the Customer Satisfaction Index (CSI), which evaluates satisfaction across five (5) dimensions: usability, information quality, assurance, reliability, and data accessibility. This method's result shows a value of 83.64%, which means the XYZ website performance is in the "Very Satisfied" category. These findings suggest that XYZ Company's website is highly effective and has a "Very Satisfied" result category in meeting user needs, paving the way for continued success in their mission to assist Indonesian students in pursuing global education opportunities